Singular perturbations and cloaking illusions for elastic waves in membranes and Kirchhoff plates. (September 2015) - Jones, I.S.; Brun, M.; Movchan, N.V.; Movchan, A.B.
Abstract: A perturbation approach is used for analysis of a near-cloak in shielding a finite scatterer from an incident flexural wave. The effect of the boundary conditions on the interior surface of the cloaking layer is analysed in detail, based on the explicit analytical solutions of a wave propagation problem for a membrane as well as a Kirchhoff flexural plate. It is shown that the Dirichlet boundary condition on the interior contour of the cloak significantly reduces the cloaking action in the membrane case, and it also makes cloaking impossible for flexural waves in a Kirchhoff plate.